A review of pomegranate supplementation: A promising remedial avenue for Alzheimer's disease - Aman Ullah; Asif Khan; Sagheer Ahmed; Hafiz Muhammad Irfan; Amin A. Hafiz; Kainat Jabeen; Mubarak Alruwaili; Muteb Alotaibi; Waiel Al Naeem; Ajmal Khan; Ahmed Al-Harrasi (Heliyon, 2023)
Neurodegenerative complications, like Alzheimer's disease (AD) exert adverse effects i.e. psychological and physiological in the central nervous system. The synthetic drugs used for these complications have negative effects on body health and therefore natural remedies are a good and targeted approach to counter such complications. Alternatively, fruits and a variety of biochemicals which are an important source of diet, can be used for remedial purposes. Due to the antioxidant properties of polyphenolic compounds, several companies utilize this property to advertise polyphenol-rich beverages. Pomegranate (Punica granatum L.), is one such fruit that is well known for its medical usage due to its antioxidant properties. In the cuurent study a literature search survey was performed on traditional uses, phytochemicals on pomegranate and their medical applications especaily in neurodegenerative deasese using electronic data bases like PubMed, Google Scholar, Scopus, Science Direct Wikipedia and Springer Nature. Based on previous preclinical and clinical studies, pomegranate juice, extracts, and its bioactive constituents have shown many mitigating properties, including suppression of inflammatory cell signaling, reduction in expression of genes associated with oxidative stress as well as pro-inflammatory cytokines in neurons, decreased production of inflammatory and oxidative stress biomarkers and increased expression of endothelial nitric oxide synthase. It also decreases the expression of soluble amyloid protein procurer β (sAPPβ), β-secretase and carboxyl terminal fragment β (CTFβ). Similarly, during an in-vivo study on APP/PS1 mice, pomegranate supplementation has been shown to impart cognitive aid by the protection of neurons and triggering neurogenesis through anti-inflammatory signaling pathway. In conclusion, pomegranate supplementation can be a promising source of protection against Alzheimer's disease.